Padang State University Early Childhood Teacher Education Program International Class: Preparing Global Competitive Teacher Candidates - Syahrul Ismet; Rismareni Pransiska (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The research was based on the phenomenon carried out by the international class program at Padang State University as a form of world class university (WCU) policy. The study aimed to describe how the implementation of international class policies. Descriptive qualitative research methods, carried out in international classes Early Childhood Teacher Education Faculty of Education, Padang State University in 2019. Data were collected through observation, interviews and documentation studies. The results showed that the implementation of the International Class Program for Early Childhood Teacher Education at the Padang State of University aimed at preparing PAUD teachers who were relevant to current needs and able to compete in the era of globalization, preparing candidates for global competitiveness with the following steps: 1) setting the vision and mission to become tertiary institutions excels in Southeast Asia. 2) selecting qualified prospective teacher inputs; 2) the recovery process applies a foreign language; 3) carry out recharge cooperation for students in overseas schools and colleges; 4) development of networks between universities in Asia; 5) audit the quality of learning. The results of this study are useful for stakeholders in universities who will develop international class programs. The results of this study get a new picture of the steps of developing international class programs that are relevant to the preparation of prospective teachers who are globally competitive. AbstrakPenelitian dilatarbelakangi fenomena dilaksanakan program kelas internasional di Universitas Negeri Padang sebagai wujud kebijakan word class university (WCU).Penelitian bertujuan mendeskripsikan bagaimana implementasi kebijakan internasional class tersebut. Metode penelitian deskriptif kualitatif, dilaksanakan di kelas internasional Pendidikan Guru Anak usia Dini Fakultas Ilmu Pendidikan Universitas Negeri Padang tahun 2019. Data dikumpulkan melalui observasi, interview dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan program kelas InternasionalPendidikan Guru Anak Usia DiniUniversitas Negeri Padang bertujuan menyiapkan guru PAUD yang relevan dengan kebutuhan kekinian serta mampu bersaing pada era globalisasimempersiapkan calon berdaya saing global dengan langkah-langkah: 1) menetapkan visi dan misi menjadi perguruan tinggi unggul di Asia Tenggara. 2) menyeleksi inputcalon guru yang bermutu; 2) proses perkulihan menerapkan bahasa asing; 3) melaksanakan kerjasama rechargebagi mahasiswa di sekolah dan perguruan tinggidi luar negeri; 4) pengembangan jejaring antar perguruan tinggi di Asia; 5) melakukan audit mutu permbelajaran. Hasil penelitian ini berguna bagi stakeholder di perguruan tinggi yang akan mengembangkan program kelas internasional. Hasil penelitian ini mendapatkan gambaran baru tentang langkah-langkah pengembangan program kelas internasional yang relevan dengan penyiapan calon guru yang berdaya saing global.